Prognostic significance of alkaline phosphatase activity and callus volume in operatively treated bone fractures - Muljačić, Ante, liječnik (Array, 2020)
Total and bone alkaline phosphatase are indicators of bone formation, a process essential in bone healing. The aim of this study was to assess the relationship of both total and bone alkaline phosphatase with the course and features of healing in surgically treated long bone fractures as compared to the callus volume. In this study, total and bone alkaline phosphatase levels and the callus volume were measured in two patients with long bone fractures. Fracture healing was rapid in one patient and slow in the other. Depending on the healing outcome, on day 7 an increase in the case of slow healing and a decrease in the case of rapid healing was noted for both total and bone alkaline phosphatase. In the case of slow healing, the callus volume was significant whereas in the case of rapid healing the callus was almost invisible on day 7. This result indicates a possible prognostic significance of aforementioned clinical biochemical and radiographic parameters in the monitoring of long bone fracture healing.